2010
DOI: 10.1111/j.1747-0285.2010.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Research Article: Insights into the Molecular Requirements for the Anti‐obesity Activity of a Series of CB1 Ligands

Abstract: Two-dimensional and 3D quantitative structureactivity relationships studies were performed on a series of diarylpyridines that acts as cannabinoid receptor ligands by means of hologram quantitative structure-activity relationships and comparative molecular field analysis methods. The quantitative structure-activity relationships models were built using a data set of 52 CB1 ligands that can be used as anti-obesity agents. Significant correlation coefficients (hologram quantitative structure-activity relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…The present work was aimed to identify essential structural features for peripherally acting CB1 receptor antagonists. Active (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) indicated that the predicted activities are very close to the actual activities (Table 6). On the basis of threshold value (active > 7.5, inactive < 7.5), sensitivity of the best model was observed as 88.89% indicating that 88.89% of compounds were correctly predicted "actives" out of the total "actives" whereas specicity was observed as 100% which indicated that 100% of compounds were correctly predicted "non-actives" out of the total "inactives".…”
Section: Pharmacophore Modelingmentioning
confidence: 80%
See 2 more Smart Citations
“…The present work was aimed to identify essential structural features for peripherally acting CB1 receptor antagonists. Active (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) indicated that the predicted activities are very close to the actual activities (Table 6). On the basis of threshold value (active > 7.5, inactive < 7.5), sensitivity of the best model was observed as 88.89% indicating that 88.89% of compounds were correctly predicted "actives" out of the total "actives" whereas specicity was observed as 100% which indicated that 100% of compounds were correctly predicted "non-actives" out of the total "inactives".…”
Section: Pharmacophore Modelingmentioning
confidence: 80%
“…The dataset so obtained was divided into a model-building set containing 25 compounds (1-25) as shown in Fig. 1 and an external test set of 10 compounds (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) which were used for the validation of the developed model as shown in Fig. 2.…”
Section: Selection Of Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…A crucial step in the generation of the CoMFA model is the 3D molecular alignment of the data set [30] , [31] . As mentioned before, the 3D alignment used in this study was based on the molecular docking of the inhibitors in the enzyme active site.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, new PPARδ‐selective agonists should be developed to help treat several diseases, such as diabetes, metabolic syndrome and atherosclerosis (22). Ligand‐ and structure‐based strategies have been previously employed to develop new bioactive ligands (34–39). In this study, we have used ligand‐ and structure‐based methodologies to identify the most important electronic, hydrophobic and structural features in determining the PPARδ/α selectivity of a series of bioactive ligands.…”
mentioning
confidence: 99%